The Effect of Institutional Share Ownership, Ownership Structure, and Corporate Social Responsibility on Environmental Sustainability in Energy Companies in Indonesia - Judijanto, Loso; Mufrihah, Mazayatul; Silalahi, Harlen; Barus, Berlin (West Science Social and Humanities Studies, 2024)
This research investigates the complex interplay between institutional share ownership, ownership structure, corporate social responsibility (CSR), and environmental sustainability in the context of Indonesian energy companies. A quantitative analysis utilizing structural equation modeling was employed to analyze data from a sample of 150 energy firms. The results reveal significant positive relationships: higher levels of CSR, increased institutional share ownership, and a more concentrated ownership structure are associated with improved environmental sustainability practices. These findings contribute to the understanding of the factors shaping environmental responsibility in the Indonesian energy sector, offering practical insights for companies and policymakers.